Bacteriological Stydy of pseudomonas aeruginosa Isolate from some pathogenic cases at diwaniya teaching hospital and hospital for obstetrics and pediatrics and its sensitivity to some antibiotics - j.m, AL-abedey S.; B.M.M , AL-muhna ‎; J.R.E, AL- shwelly (The Iraqi Journal of Veterinary Medicine, 2009)
The aim of this study was to determine the important role of Pseudomonas aeruginosa in secondary infection of hospitalized patients, and test the sensitivity of this bacteria to some antibiotics were used in treatment of its infection .90 samples were collected from different cases in Diwanya teaching hospital ,maternity & children hospital .The results show isolation of 29 isolates 0f Pseudomonas aeruginosa (32.2%) .Microscopic examination,cultural characteristic on selective and differential media and biochemical testing were used in the diagnosis of this bacteria.The sensitivity test of this bacteria to some antibiotics was done by using disc diffusion method .Allisolates were resistant to ampicillin (100%),while it gave high sensitivity to ciprofloxacin(2.3%).